2012
DOI: 10.1099/mic.0.054726-0
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudomonas aeruginosa rmlBDAC operon, encoding dTDP-l-rhamnose biosynthetic enzymes, is regulated by the quorum-sensing transcriptional regulator RhlR and the alternative sigma factor σS

Abstract: The Pseudomonas aeruginosa rmlBDAC operon, encoding dTDP-L-rhamnose biosynthetic enzymes, is regulated by the quorum-sensing transcriptional regulator RhlR and the alternative sigma factor s Pseudomonas aeruginosa produces as biosurfactants rhamnolipids, containing one (monorhamnolipid) or two (di-rhamnolipid) L-rhamnose molecules. The rhamnosyltransferase RhlB catalyses the synthesis of mono-rhamnolipid using as precursors dTDP-L-rhamnose and 3-(3-hydroxyalkanoyloxy)alkanoic acids (HAAs) produced by RhlA, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…In addition, we found that the rhlA‐ las‐box mutant C12T is no longer bound by RhlR in the absence of C4‐HSL. This is similar to the way that RhlR interacts with the lecA‐ las‐box (Table ), but differs with the reported ability of this protein to interact with the rhlA‐ and rmlB‐ las‐boxes in the absence of this autoinducer (Medina et al ., ; Aguirre‐Ramírez et al ., ). As both the rhlA‐ and the rmlB‐ las‐boxes contain a C in position 12, it is possible that RhlR without autoinducer only binds to las‐boxes that contain a C in position 12, and not to those containing a T in this position, while RhlR/C4‐HSL can interact with las‐boxes containing either of these nucleotides in position 12.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, we found that the rhlA‐ las‐box mutant C12T is no longer bound by RhlR in the absence of C4‐HSL. This is similar to the way that RhlR interacts with the lecA‐ las‐box (Table ), but differs with the reported ability of this protein to interact with the rhlA‐ and rmlB‐ las‐boxes in the absence of this autoinducer (Medina et al ., ; Aguirre‐Ramírez et al ., ). As both the rhlA‐ and the rmlB‐ las‐boxes contain a C in position 12, it is possible that RhlR without autoinducer only binds to las‐boxes that contain a C in position 12, and not to those containing a T in this position, while RhlR/C4‐HSL can interact with las‐boxes containing either of these nucleotides in position 12.…”
Section: Resultsmentioning
confidence: 97%
“…The 5′ untranslated region (5′‐UTR) of the rmlBDAC operon that encodes the enzymes that convert glucose‐1‐phosphate to TDP‐L‐rhamnose (the substrate for the synthesis of rhamnolipids) contains a sequence where RhlR binds specifically (rhl‐box), both in the presence and in the absence of C4‐HSL; this rhl‐box has the sequence: AC CT ACCA G ATCTGGGGTTG (Aguirre‐Ramírez et al ., ). Thus, the rmlB‐ rhl‐box lacks the A at position 17 and the G at position 18 that was proposed to be invariable for las‐boxes (Whiteley & Greenberg, ).…”
Section: Introductionmentioning
confidence: 97%
“…; Aguirre‐Ramirez et al. ). These sites could serve as recognition sequences for effectors that downregulate opdQ transcription during hypoxic growth.…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to the complexity of the genetically regulated pathways controlling in vivo RL production and/or the inability of efficiently controlling heterologous gene expression leading to metabolic perturbations. In fact, expression of rmlBDAC , rhlAB and rhlC in P. aeruginosa is mainly regulated by the rhl quorum sensing system , which in turn is part of a complex genetic regulation cascade . According to a previous report , RhlA is overexpressed in cultures optimized for the overproduction of RLs, suggesting that RhlA acts as a key enzyme providing the lipidic flux toward the RL biosynthesis pathway.…”
Section: Introductionmentioning
confidence: 99%